1996
DOI: 10.1016/0029-7844(96)00020-8
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Individual Computer Heart Rate Indices in Detecting Acidemia at Birth in Growth-Restricted Fetuses

Abstract: In this population of growth-restricted fetuses delivered by elective cesarean, the computer indices of duration of episodes of low variation and short-term and long-term variation were significantly associated with umbilical artery pH and predicted umbilical artery acidemia at birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(41 citation statements)
references
References 13 publications
3
34
0
4
Order By: Relevance
“…Our results agree with some previous studies (Dalton et al 1983;Druzin et al 1986;Serra et al 2009), confirming that there is a significant change in foetal condition throughout gestation by the synergic action elicited by the Autonomic Nervous System (ANS) activity, through its sympathetic and parasympathetic branches (Pillai and James 1990;Guzman et al 1996). The most evident modification consists of a significant decrease of baseline FHR during gestational age, which reflects the normal foetal neural maturity, because the progressive increase in the parasympathetic influence on foetal heart rate results in a gradual lowering of baseline rate.…”
Section: Discussionsupporting
confidence: 92%
“…Our results agree with some previous studies (Dalton et al 1983;Druzin et al 1986;Serra et al 2009), confirming that there is a significant change in foetal condition throughout gestation by the synergic action elicited by the Autonomic Nervous System (ANS) activity, through its sympathetic and parasympathetic branches (Pillai and James 1990;Guzman et al 1996). The most evident modification consists of a significant decrease of baseline FHR during gestational age, which reflects the normal foetal neural maturity, because the progressive increase in the parasympathetic influence on foetal heart rate results in a gradual lowering of baseline rate.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have revealed that heart rate reduction in the fetus and the presence of repeated late decelerations in CTG traces performed intrapartum are related to fetal hypoxia. Moreover, STV below 3 ms regarded as worsening of fetal well-being is highly correlated with the grade of hypoxia, acidosis, and the risk of intrauterine death [14][15][16]. Anseschi et al in their study proved that a value of STV below 4.5 ms along with other risk factors may be regarded as a threshold below which timing of delivery should be considered in order to improve perinatal outcomes in pregnancies complicated by IUGR [17].…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were performed on high risk pregnancies 10,11,23,25,26 , one on low-risk 24 and one included both high and low risk populations 22 . Amongst high-risk pregnancies, 4 studies observed a predictive relationship of STV for neonatal acidaemia in intrauterine growth restricted (IUGR) fetuses 10,11,23,26 . However, all studies excluded fetuses with chromosomal and structural anomalies.…”
Section: Resultsmentioning
confidence: 99%
“…An initial search of 398 citations, identified 7 primary articles 10,11,[22][23][24][25][26] 24 where no such record was found. Five studies were performed on high risk pregnancies 10,11,23,25,26 , one on low-risk 24 and one included both high and low risk populations 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation